Estimating carbon emissions for REDD+. The conditions for involving local people - Boissière, Manuel; Felker, Liz; Beaudoin, Guillaume; Bong, Indah Waty; Dharmadi Hawthorne, Sandra; Depuy, Walker H.; Ekowati, Dian; Farida, Lina; Hofstee, Carola; Vega Praputra, Andhika; Rafanoharana, Serge; Aria Seta, Gilang; et al. (Perspective, 2014)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"The participation of local people in climate change mitigation is considered key to ensuring that their priorities are taken into account. This should help to design effective social safeguards and to improve equity in benefit sharing. The participation of local people has been explored in carbon emission Measurement, Reporting and Verification (MRV) for REDD+. The feasibility and sustainability of participatory MRV (PMRV) are not automatic and depend on its relevance to local people (including incentives to participate), their technical capacity and the existence of appropriate structures for MRV."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"The participation of local people in climate change mitigation is considered key to ensuring that their priorities are taken into account. This should help to design effective social safeguards and to improve equity in benefit sharing. The participation of local people has been explored in carbon emission Measurement, Reporting and Verification (MRV) for REDD+. The feasibility and sustainability of participatory MRV (PMRV) are not automatic and depend on its relevance to local people (including incentives to participate), their technical capacity and the existence of appropriate structures for MRV."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">The participation of local people in climate change mitigation is considered key to ensuring that their priorities are taken into account. This should help to design effective social safeguards and to improve equity in benefit sharing. The participation of local people has been explored in carbon emission Measurement, Reporting and Verification (MRV) for REDD+. The feasibility and sustainability of participatory MRV (PMRV) are not automatic and depend on its relevance to local people (including incentives to participate), their technical capacity and the existence of appropriate structures for MRV.